1999
DOI: 10.1191/074823399678846619
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides and adjuvants: an evolving view

Abstract: The present report examines the in vitro genotoxicity (micronucleus assay) of herbicides and adjuvants and reports on an in vivo human study on potential endocrine effects of pesticides, including herbicides. Adjuvants are used in conjunction with 2,4-dichlorophenoxy acetic acid (2,4-D) and other herbicides. Earlier pesticide applier survey results (n = 709) show that 59% of the applicators used adjuvants, and the majority of this group used paraffinic oils and/or surfactant mixtures. As a beginning effort to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Both 2,4-D and MCPA, the exposure of interest in the current study, and the potential contaminant, dioxins, are endocrine disruptors (1,42). In addition, adjuvants used in the application of 2,4-D to spring wheat also have endocrinedisrupting characteristics (45). In the IARC occupational cohort, there was a slight, nonstatistically significant increase in prostate cancer mortality (6).…”
Section: Resultsmentioning
confidence: 78%
“…Both 2,4-D and MCPA, the exposure of interest in the current study, and the potential contaminant, dioxins, are endocrine disruptors (1,42). In addition, adjuvants used in the application of 2,4-D to spring wheat also have endocrinedisrupting characteristics (45). In the IARC occupational cohort, there was a slight, nonstatistically significant increase in prostate cancer mortality (6).…”
Section: Resultsmentioning
confidence: 78%
“…These data suggest that the majority of the commercial chlorophenoxy products studied were not genotoxic at the chromosomal level (8).…”
mentioning
confidence: 69%
“…With further review, we noted that adjuvants are sometimes used in conjunction with chlorophenoxy herbicides in roadside and other applications. We found that four out of four adjuvants induced significant increases in the frequency of micronuclei (8). Two of five adjuvants showed evidence of weak endocrine-disrupting activity in MCF-7 cells (9).…”
mentioning
confidence: 97%
“…Occasionally 2,3,7,8-tetrachlorodibenzo-pdioxin may be present in technical grade 2,4-D (Johnson et al 1992). Adjuvants may contribute to adverse health effects (Garry et al 1999). In vitro assays showed that commercial grade 2,4-D at concentrations of 1 and 10 µg/mL caused cell proliferation, whereas assays with reagent grade 2,4-D did not.…”
Section: Discussionmentioning
confidence: 99%